Primary Mediastinal Synovial Sarcoma; a rare case - Ali Goudarzi; Leila Ostovar (Journal of Cardio-Thoracic Medicine)
Background: Synovial sarcoma, a rare subtype of soft-tissue sarcomas, typically manifests in the extremities of young individuals. Mediastinal occurrences are exceedingly uncommon, with sparse cases documented.Case: This article details the atypical presentation of a mediastinal synovial sarcoma in a 68-year-old female patient, diverging from the common demographic and anatomical predilections. Initial symptoms of a dry cough and fatigue led to the discovery of a mediastinal mass via chest CT scan. Subsequent pathological examination confirmed the diagnosis of mediastinal synovial sarcoma. Despite the identification of this rare tumor, the patient's condition progressed rapidly, resulting in her demise within two months post-diagnosis.Conclusion: This case underlines the critical need for increased awareness and research into the mediastinal variant to improve diagnostic accuracy and treatment efficacy. Despite synovial sarcoma being predominantly identified in the extremities, occurrences in the mediastinum present unique diagnostic dilemmas and therapeutic hurdles due to limited literature and atypical clinical presentations. The utilization of advanced imaging modalities, immunostaining techniques, and multimodal treatment approaches is essential in the management of mediastinal synovial sarcoma.